Efficacy and Safety of Adalimumab and Secukinumab in Erythrodermic Psoriasis: A Single Centre Retrospective Study - Yachen Wang; Rishna Malla; Fengling Yang; Hanjing Yin; Suju Luo (Indian Journal of Dermatology, 2025)
Erythrodermic psoriasis (EP) is a rare but severe form of psoriasis. Conventional treatments are often ineffective and challenging to maintain; however, new biologic medications have shown promise in the management of EP with limited evidence. To assess the efficacy and safety of two biological treatments, adalimumab and secukinumab, in patients with EP. This single centre study was performed from 8 August 2019 to 12 June 2023. Patients demonstrating psoriasis involving over 75% of body surface area were included. The psoriasis area severity index (PASI) score was recorded during follow-up. A total of 20 patients fulfilling the diagnostic criteria for EP were enrolled in the study. At week 24, 50% improvement of PASI (PASI50), PASI75, PASI90 and PASI100 was reached in 95%, 65%, 45% and 15% of patients, respectively. Adalimumab and secukinumab elicited similar PASI responses. The percentages of PASI responders with comorbidities were lower than that of their counterparts in general. Minor adverse events occurred in 30% of patients, and none was forced to suspend the corresponding drug. A remarkable efficacy was demonstrated by adalimumab and secukinumab in treating EP, with rapid and substantial clinical improvement observed in the majority of patients. Both had a well-tolerated safety profile. However, secukinumab seemingly manifested superior response rates than adalimumab in patients with comorbidities.